2014
DOI: 10.1038/nature13960
|View full text |Cite
|
Sign up to set email alerts
|

An enteric virus can replace the beneficial function of commensal bacteria

Abstract: Intestinal microbial communities have profound effects on host physiology1. Whereas the symbiotic contribution of commensal bacteria is well established, the role of eukaryotic viruses that are present in the gastrointestinal tract under homeostatic conditions is undefined2,3. Here, we demonstrate that a common enteric RNA virus can replace the beneficial function of commensal bacteria in the intestine. Murine norovirus (MNV) infection of germfree or antibiotics-treated mice restored intestinal morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
369
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(400 citation statements)
references
References 38 publications
18
369
1
5
Order By: Relevance
“…No circoviruses have yet been linked to human diseases. Our observation of greater abundance and prevalence of Circoviridae-related sequences in controls suggests that infection with the virus offers benefits to the host, as observed in animal models for other viruses (22)(23)(24) and might offer protection from the development of autoimmune diabetes, as has been shown in animal studies for other types of viruses (25,26). However, the sample size in terms of number of subjects is small in this cohort, and these sequences were not detected in every control subject.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…No circoviruses have yet been linked to human diseases. Our observation of greater abundance and prevalence of Circoviridae-related sequences in controls suggests that infection with the virus offers benefits to the host, as observed in animal models for other viruses (22)(23)(24) and might offer protection from the development of autoimmune diabetes, as has been shown in animal studies for other types of viruses (25,26). However, the sample size in terms of number of subjects is small in this cohort, and these sequences were not detected in every control subject.…”
Section: Discussionsupporting
confidence: 54%
“…In a recent study, CrAssphage, a human bacteriophage, was correlated with Bacteroides dorei, but a direct association of this virus with islet autoimmunity was not observed (21). Importantly, although it generally has been assumed that viruses cause harm by triggering diseases, studies in animal models show that virus infection is not necessarily harmful and can provide symbiotic benefits (22)(23)(24), and actually may offer protection from the development of T1D (25,26). Thus, an evaluation of the virome in children at risk for T1D might have the potential to identify viruses associated with either disease risk or protection from disease.…”
mentioning
confidence: 99%
“…Overall, our recent findings expand the cellular targets of NoVs to now include innate and adaptive immune cells. Moreover, our work together with studies by Kernbauer et al 48 and Baldridge et al 49 illuminate a previously unappreciated role for commensal bacteria as co-factors for NoV infection.…”
Section: Utility Of a Human Norovirus Cell Culture Systemsupporting
confidence: 72%
“…Because virus titers were reduced but not eliminated completely, we presume that bacteria stimulate MuNoV infection but are not absolutely required. Since the publication of our original article, Kernbauer et al reported similar reductions in MuNoV titers in germ-free mice 48 and Baldridge et al reported that commensal bacteria facilitate persistent MuNoV infections. 49 Thus, commensal bacteria stimulate HuNoV infection of cultured B cells as well as acute and persistent MuNoV infection in vivo.…”
Section: Commensal Bacteria Facilitate Norovirus Infectionsmentioning
confidence: 69%
“…The function of viruses in the healthy gut and in gastrointestinal disease is not well defined; however, a number of studies suggest an important role. It has been demonstrated that a common enteric RNA virus can replace the beneficial function of commensal bacteria in the intestine [108]. In that study, infection of germ-free or antibiotic-treated mice with murine norovirus (MNV) restored intestinal morphology and lymphocyte function without inducing overt inflammation.…”
Section: The Gut Virome and Ibdmentioning
confidence: 99%